The Transformational Trends of New Trade Unions’ Activities and Functions in New Uzbekistan - Ibrohimovich, Kamolov Ilhomjon (Indonesian Journal Publisher, 2025)
This study examines the transformational trends of trade unions’ activities and functions in the context of New Uzbekistan. The main objective is to analyze how trade unions, as institutions of civil society, adapt to ongoing political, social, and economic reforms while maintaining their role in protecting the socio-economic interests of workers. The study employs a qualitative and analytical approach, drawing on legal frameworks, policy documents, and international experiences of trade union development. The findings reveal that the adoption of the Law “On Trade Unions” (2019) and the recent constitutional reforms have significantly expanded the rights and opportunities of trade unions, strengthening their independence and enhancing their role in social partnership. Furthermore, trade unions in Uzbekistan are increasingly aligning their practices with international labor standards and building regional cooperation, particularly through the Council of Trade Unions of Central Asian Countries. In conclusion, the study highlights that New Trade Unions in Uzbekistan are not only organizationally restructured but also functionally redefined to address modern challenges such as globalization, digitalization of work, and labor market transformations. These changes indicate that trade unions are becoming an important factor in building a democratic society and ensuring social justice in New Uzbekistan.